2006
DOI: 10.1055/s-2006-947178
|View full text |Cite
|
Sign up to set email alerts
|

A New Triterpene and Anti-Hepatitis B Virus Active Compounds from Alisma orientalis

Abstract: A new triterpenoid named alisol O ( 1) was isolated from the rhizomes of Alisma orientalis, together with six known compounds: alisol A 24-acetate ( 2), 25-anhydroalisol A ( 3), 13 beta,17 beta-epoxyalisol A ( 4), alisol B 23-acetate ( 5), alisol F ( 6), and alisol F 24-acetate ( 7). Based on 1D and 2D-NMR data (HMQC, HMBC, COSY, ROESY), the structure of the new compound was deduced to be 11-dehydroxy-12-dehydroalisol F-24-acetate ( 1). Compounds 2 - 7 exhibited inhibitory activity in vitro on hepatitis B viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…Protostane triterpenes from Alisma orientalis have also been reported for their anti-HBV activity. Compound 7 in particular showed promising effects, inhibiting HBsAg and HBeAg with an IC50 of 7.7 µmol/L and 5.1 µmol/L, respectively, whereas cytotoxicity was only observed at a much higher concentration [50% cytotoxicity concentration (CC50)=142.7 µmol/L] [39] . Among the 10 different alkaloids isolated from Corydalis saxicola, a traditional herb used as folk medicine to treat hepatitis in China, dihydrochelerythrine was shown to exhibit extraordinary effects against HBsAg and HBeAg secretions.…”
Section: -Arylbenzofuran Derivativesmentioning
confidence: 99%
“…Protostane triterpenes from Alisma orientalis have also been reported for their anti-HBV activity. Compound 7 in particular showed promising effects, inhibiting HBsAg and HBeAg with an IC50 of 7.7 µmol/L and 5.1 µmol/L, respectively, whereas cytotoxicity was only observed at a much higher concentration [50% cytotoxicity concentration (CC50)=142.7 µmol/L] [39] . Among the 10 different alkaloids isolated from Corydalis saxicola, a traditional herb used as folk medicine to treat hepatitis in China, dihydrochelerythrine was shown to exhibit extraordinary effects against HBsAg and HBeAg secretions.…”
Section: -Arylbenzofuran Derivativesmentioning
confidence: 99%
“…The 1 H-and 13 C-NMR spectra (Table 1) showed signals for one oxymethine, one oxygen quaternary carbon, five tertiary methyls, and a 1,2,4-trisubstituted aromatic ring, which suggested that compound 1 was an abietane diterpenoid substituted by two hydroxy groups. The heteronuclear multiple bond connectivity (HMBC) correlations of H-C (16) and H-C(17) (d H 1.58, 2H 3 ) with the oxygen quaternary carbon C(15) (d C 72.3, s) confirmed that one hydroxy group was located at C (15). Furthermore, correlations H-C(3)/C(1), C (2) and C(4), and H-C(5)/C(3) in the HMBC spectrum of 1 confirmed the other hydroxy group to be positioned at C(3).…”
Section: Resultsmentioning
confidence: 99%
“…The formazan crystals were redissolved and the absorbance was measured on a microplate reader at 490 nm. 16) Cytotoxicity Testing Cells were seeded in 96-well plates, treated with indicated concentrations of tested compounds or a positive control compound, Etoposide (VP-16; Jiangsu Hengrui Medicine Co., Ltd.). After incubation for 24 h at 37°C, 20 ml/well of MTT (5 mg/ml) was added and cells were incubated for an additional 4 h. Then, "triplex solution" (10% sodium dodecyl sulfate (SDS), 5% isobutanol, 12 mM HCl) was added to dissolve the formazan crystals overnight.…”
Section: Methodsmentioning
confidence: 99%
“…is widely cultivated in China and Japan, and the dried rhizomes are a crude drug for the treatment of diabetes and diuretics. 1) Our previous paper 2) reported that a serious protostane-type triterpenes extracted from this plant showed anti-hepatitis B virus (HBV) activity. As a subsequent study on this plant, further investigation on the less polar part of the 90% EtOH extract of the dried rhizomes of A. orientalis led to the isolation of two new sesquiterpenes: alismorientols A (1) and B (2) (Fig.…”
mentioning
confidence: 99%